THE USE OF PICTURE SERIES IN WRITING PROCEDURE TEXT - Yessy Listyaningsih (Language and Education Journal, 2016)
Writing is one of skill which needs to be learned by the students. Through writing, someone can share personal meanings and express his/her idea in the written form. However, students still have problems in writing procedure text. Therefore, the purpose of this study was to find out whether there was a statistically significant difference of students’ writing achievement and that of those who were not. This research was quantitative. The samples of the research were 30 students at the eighth grade of SMP Negeri 4 Kayuagung, namely classes VIII.3 and VIII.6. The instrument used was written test in the form of essay. The data were analyzed by using t-test. The result showed that there was a statistically significant difference on students’ writing of procedure text with significance level of p<0.05 and the value of tobtained (3.189) was higher than ttable (2.000). This suggested that picture series helped the students to understand the difficult words easily by looking at the pictures, made them more enjoyable and interesting to learn writing, made the class more active and alive, and could attract the students’ curiosity in learning new vocabulary so that they could write the composition of procedure text well